Efektivitas Metode Hafalan dalam Mengajarkan Doa Harian kepada Anak SDN No.179/1 Ladang Peris - Arafik, Arafik; Holipah, Holipah; Pioloka, Pinda (TSAQOFAH, 2025)
This study examines the effectiveness of memorization methods in teaching daily prayers at SDN No. 179/1 Ladang Peris, with a focus on enhancing students' spiritual understanding. The background of this research is driven by the lack of studies that deeply explore the impact of memorization methods on understanding daily prayers, especially in the context of teaching Arabic in elementary schools. The aim of this research is to evaluate how repeating daily prayers can strengthen students' memory and deepen their understanding of the meaning of the prayers they learn. The methodology used is a literature review, analyzing various sources related to teaching daily prayers and the effectiveness of memorization methods. The findings indicate that using a structured and repetitive memorization method can improve students' ability to remember daily prayers, but strengthening the understanding of the meaning of the prayers is also necessary to deepen the students' spiritual experience. The implications of this research show that teaching methods for prayers should consider not only memorization but also deeper understanding to support students' spiritual development, as well as the importance of educational policy support and technology to facilitate more effective learning processes.